Shona women in Zimbabwe - a purchased people? : marriage, bridewealth, domestic violence, and the Christian traditions on women - Chitakure, John. (U.S.A Pickwick publications, 2016)
The position and treatment of women in every religion, culture, and society have been subjects of concern for a long time. In every society, women fight for their emancipation from exploitive and oppressive patriarchal structures. The most contentious issues include domestic violence, gender discrimination and inequality in the areas of employment, leadership, and marriage. Domestic violence tops the list and is the worst enemy of any progressive and democratic society. It dehumanizes, disfigures, and demeans its victims and survivors. Shona Women in Zimbabwe--a Purchased People explores the causes of domestic violence--the cultural practice of bridewealth, in particular--and assesses the extent to which it contributes to the proliferation of domestic violence among the Shona people of Zimbabwe. It then explores the Christian traditions, particularly, the Roman Catholic Church, in search of resources that can be used to emancipate Shona women from patriarchal subjugation. Finally, the book offers a pastoral response that is informed by the experiences of the Shona women, their cultural resources, and the Roman Catholic religious tradition. -- back cover.
Includes bibliographical references (pages 143-147) and index.
Keywords: Catholic Church -- Zimbabwe; Women, Shona -- Zimbabwe -- Social conditions; Women -- Violence against -- Zimbabwe